Islamic Education Learning to Develop Emotional Intelligence (EQ) for Students with Autism Spectrum Disorder (ASD) - Sigit Raharja (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2024)
This study aims to describe the role of Islamic Religious Education (IRE) teachers in developing the emotional intelligence (EQ) of autistic students at SLB Mitra Ananda through the applied learning methods and media. This study uses a field research method to deeply understand the role of IRE teachers in developing the EQ of autistic students. The results of the study indicate that the development of EQ of autistic students in IRE learning is carried out through: (1) the implementation of an Individualized Education Program (IEP) which includes assessment, program planning, and outcome evaluation; (2) the integration of IRE learning with a snoozelen room to create a calm and stable atmosphere; (3) teacher's exemplary behavior based on the morals of Prophet Muhammad SAW; (4) collaborative activities such as prayer and congregational prayer to improve discipline, patience, concentration, empathy, and cooperation; (5) relaxation techniques with an Islamic approach, including audio-visual based learning, receptive and expressive language communication, and training to recognize one's own and other people's emotions; (6) murotal Al-Qur'an meditation in a relaxed atmosphere; and (7) positive reinforcement through social guidance which includes problem solving and routine habituation.